Examining predictors of loneliness among Older Americans Act National Family Caregiver Support Program participants - Heather L. Menne; Claire Pendergrast (Frontiers Media S.A., 2024)
Family caregivers may be at particular risk for social isolation and loneliness. Multiple factors can impact caregivers' health and well-being outcomes, including loneliness. Guided by an adaptation of the Stress Process Model of Caregiving, this study uses the 2019 National Survey of Older Americans Act Participants (NSOAAP)-Family Caregiver Support module to inform efforts to reduce loneliness through family caregiver support programs. A hierarchical multiple regression model reveals that caregivers who report more loneliness are more likely to be female, Hispanic, living alone, not a child or other caregiver of the care recipient, have a care recipient with 3+ ADL needs, experience more social life conflict related to caregiving, experience less joy in caregiving, feel less appreciated by the care recipient, feel less support in caregiving, and attend counseling. This study helps advance the goals of the National Strategy to Support Family Caregivers, and the findings underscore the importance of continuing and expanding efforts to address loneliness and related well-being outcomes among family caregivers.